Implementation of Notary's Principle of Prudence in Making Authentic Deeds Between Housing Developers, Banks and Home Buyers in Ngawi Regency - Wahyuningrum, Widhiastuti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Notaries in carrying out their duties and positions are very important to implement the principle of caution in the process of making authentic deeds, considering the frequent legal problems with authentic deeds made by notaries because there are parties who commit crimes such as providing fake letters and false statements into the deeds made by notaries. The objectives of this thesis research are: 1) To find out and analyze the urgency of the notary's principle of caution in making authentic deeds of housing developer credit agreements; 2) To find out and analyze the application of the notary's principle of caution in making authentic deeds in Ngawi Regency. The conclusion of the results of this study are: 1) The forms of precautionary principles carried out by notaries in the process of making deeds are, introducing the identity of the person appearing, verifying the subject data and carefully the object of the person appearing, giving a grace period in the process of making deeds, acting carefully, carefully and precisely in the process of making deeds, fulfilling all technical requirements for making deeds and reporting if there is an indication of money laundering in transactions at the notary, forms of precautionary principles like this should be mandatory for notaries to implement in order to prevent notaries from having legal problems with authentic deeds they make in the future. 2). Implementation of the Notary's precautionary principle in making authentic deeds in Ngawi Regency has implemented the precautionary principle and if there is falsification of letters and false information provided by the parties in the process of making deeds, then material responsibility is the responsibility of the parties who have provided false data or false information to the notary. And the parties can be prosecuted and held responsible for the Criminal Act of Forged Letters and False Statements in accordance with Articles 263, 264 and Article 266 of the Criminal Code.